Identification of the critical parts for a medium courier turboprop aircraft - Marius-Alexandru VOICU; Ion FUIOREA (INCAS Bulletin, 2020)
Each time an aircraft system fails, a series of steps are required to repair or restore the aircraft to full operational status. The steps include failure detection, fault isolation, disassembly to gain access to the defective element, repair, and so on. The frequency of the maintenance becomes a significant parameter in determining system support requirements. The maintenance frequency for a particular item depends very much on the reliability of that item. In order to exemplify this idea the present paper contains a series of analyzes whose purpose is to identify the critical parts for a medium courier turboprop aircraft operated by the Romanian Air Force.